Technoeconomic assessment of different biorefinery approaches for a spent sulfite liquor. Issue 10 (11th January 2016) - Rueda, Cristina; Marinova, Mariya; Paris, Jean; Ruiz, Gema; Coz, Alberto
Abstract: BACKGROUND: Spent sulfite liquor, a by‐product obtained in the process of manufacturing dissolving pulp, contains 26% of sugars that can be valorized in order to obtain high value‐added products by means of biorefinery processes. A technoeconomic assessment of three options, furfural, xylitol and ethanol, has been developed with the purpose of identifying which alternative is the best for the case study mill. RESULTS: Different techniques of fractionation/detoxification of the spent liquor such as ultrafiltration, resins or adsorption were tested; anionic resins were selected as the most feasible. A technical evaluation of the three biorefinery options producing 19.92, 15.84 or 14.64 t day −1 of furfural, xylitol and ethanol, respectively, was performed. The study was pursued with the sizing and costing of the equipment. For the economic evaluation, the fixed capital invested and the manufacturing costs for each valorization option were computed as well as the return period and the net present value. In addition, a sensitivity analysis was performed for the most promising option. CONCLUSIONS: Spent sulfite liquor can be profitably processed in the considered mill. According to the data obtained by simulation and the analysis performed, the best valorization option is the production of xylitol. © 2015 Society of Chemical Industry